Matrine reduces cigarette smoke-induced airway neutrophilic inflammation by enhancing neutrophil apoptosis. (18th February 2019) - Yu, Xuhua; Seow, Huei Jiunn; Wang, Hao; Anthony, Desiree; Bozinovski, Steven; Lin, Lin; Ye, Ji-Ming; Vlahos, Ross
Abstract : Chronic Obstructive Pulmonary Disease (COPD) is a major incurable global health burden and will become the third largest cause of death in the world by 2030. It is well established that an exaggerated inflammatory and oxidative stress response to cigarette smoke (CS) leads to, emphysema, small airway fibrosis, mucus hypersecretion, and progressive airflow limitation. Current treatments have limited efficacy in inhibiting chronic inflammation and consequently do not reverse the pathology that initiates and drives the long-term progression of disease. In particular, there are no effective therapeutics that target neutrophilic inflammation in COPD, which is known to cause tissue damage by degranulation of a suite of proteolytic enzymes including neutrophil elastase (NE). Matrine, an alkaloid compound extracted from Sophora flavescens Ait, has well known anti-inflammatory activity. Therefore, the aim of the present study was to investigate whether matrine could inhibit CS-induced lung inflammation in mice. Matrine significantly reduced CS-induced bronchoalveolar lavage fluid (BALF) neutrophilia and NE activity in mice. The reduction in BALF neutrophils in CS-exposed mice by matrine was not due to reductions in pro-neutrophil cytokines/chemokines, but rather matrine's ability to cause apoptosis of neutrophils, which we demonstrated ex vivo . Thus, our data suggest that matrine has anti-inflammatory actions that could be of therapeutic potential in treating CS-induced lung inflammation observed in COPD.